Single-center, retrospective study on changes in pain-relieving therapy after bone metastasis detection by bone scintigraphy in prostate cancer patients - Thamyrys Bessa Silva; Marcella Araugio Soares Cardoso; Jayda Eiras Ramim; Anke Bergmann; Priscilla Brunelli Pujatti (Universidade de São Paulo, 2022)
Abstract Whole-body bone scintigraphy (WB-BS) is used for detecting and monitoring metastatic spread of prostate cancer (PCa) and to investigate bone pain episodes. To investigate the impact of a positive WB-BS on pain-relieving medicine prescription in PCa patients, a single-center, retrospective cohort study with PCa patients classified as positive for bone metastases (BM) by WB-BS was conducted. Demographic, clinical, and ambulatory pain-relieving medicine prescription data were evaluated. Pain-relieving medicines were categorized according to the WHO 'Analgesic Ladder'. Regimens adopted before and after WB-BS were compared. Differences were considered significant at p<0.05. A total of 180 PCa patients were diagnosed with BM, 64.4% of whom were ≥65 years of age. Thirty-three patients were prescribed analgesics only after WB-BS, mostly including NSAIDs and weak opioids. Pain-relieving prescription changed after WB-BS in patients with prescriptions before and after WB-BS, with a reduction in NSAIDs and adjuvants and an increase in weak and strong opioids. In addition, 40% of patients with WHO analgesic step 1 drugs and 21.7% of patients with WHO step 2 drugs before WB-BS changed to other WHO steps after WB-BS. Pain-relieving prescriptions changed after a positive WB-BS, providing evidence that it could contribute to clinical management of painful metastatic PCa patients.